Women’s vocational education 1890–1990 in Finland and Sweden : the example of vocational home economics education - Broberg, Asa [Verfasser]; Lindberg, Viveca [Verfasser]; Wärvik, Gun-Britt [Verfasser] (My University, 2021)
"This article argues that women’s vocational education needs to be viewed in relation to the development of vocational education and training (VET) more broadly. The history of women’s VET is also a history of the term “women’s education” itself and how, almost a century after it was introduced, this term is hardly used. Instead, we see gendered vocations and vocational programmes that predominantly recruit women. The aim of this study is to investigate and compare the rise and fall of VET specifically targeting women in Finland and Sweden, in particular the kind of VET described in educational policy during the 20th century as education that was predestined for women. What societal motives underpinned the establishment and development of domestic education as VET? How can we understand the dismantling of education targeting women? Our primary sources are government inquiries concerning VET for women and previous research in this field. We argue that the reasons for the development of women’s VET reflect not only how certain social groups understood societal needs at the time, but that developing VET was a response to the increasingly significant but complex roles women played in the public arena." (Author's abstract ; BIBB-Doku)
Keywords: S 1.3 Berufliche Erstausbildung; P 1.3 Frauen; G 2.4.5 Gender Mainstreaming; I 2.2.1 Westeuropa; 370; Berufsausbildung; Frauenbildung; geschlechtsspezifische Sozialisation; Geschlechterrolle; 1890-1990; Finnland; Schweden